Development of Carbon Emission Disclosure Indicators in Indonesia and Analysis of Determining Factors - Septiani Fransisca; Bernadette Robiani; Inten Meutia; Yusnaini Yusnaini (Qubahan Academic Journal)
The first objective of this research is to develop indicators of carbon emission disclosure in Indonesia, while the second objective is to analyse the determinants of carbon emission disclosure. This research resulted in the development of carbon emission disclosure indicators. The development recommendations were derived from a review of scientific literature. The results of the recommendation are 14 theme indicators as a measure in carbon emissions disclosure and also become dependent variable of this research. Furthermore, this research analyses various determinants that affect carbon emission disclosure. There are four main groups of variables determined in this study, namely financial performance, ownership, committee, and board of directors. The scope of the research is 225 companies sample listed on the Indonesia Stock Exchange. The industry sectors that are the scope of the research are the energy sector, industrial sector, basic material sector, non-cyclical consumer sector, and transportation sector. The method used in this research is a combination of qualitative and quantitative. The development of carbon emission disclosure indicators was examined using qualitative methods through a literature review. While the determinant analysis uses quantitative methods with probability analysis (logistic regression analysis). The results showed that the group of financial performance variables (represented by leverage and market value variables), ownership (represented by International Listing and state ownership variables), committee (represented by environmental committee), and board of directors (represented by Board Diversity) on carbon emission disclosure in Indonesia have significant effects. The development of indicators and the results of this research have supported the Legitimacy theory as a basis that can influence company's carbon emissions disclosure. The novelty of carbon emissions disclosure indicator can be used as a reference for companies and regulators as a basis for complete carbon emissions disclosure.